RANCANG BANGUN APLIKASI MONITORING MANAJEMEN KAUANGAN PROYEK KONTRUKSI BERBASIS ANDROID PADA PT. BEGAWAN POLOSORO - Marcelino Wiranto; Aslan Alwi; Andy Triyanto (KOMPUTEK, 2020)
Regional development efforts carried out by utilizing the APBD by the government in Indonesia in various fields ranging from procurement of goods, construction work, consulting services for business entities, individual consulting services and others according to the needs of each government agency involve local and foreign companies operating in various fields. to compete in winning projects auctioned off by the government on the official website of the LPSE (Electronic Procurement Service). One of the companies engaged in the procurement of construction goods and services, namely PT. Begawan Polosoro. Employees who have excessive work such as overtime and out of town assignments are also poorly monitored so that in the payroll process sometimes the bonuses are not given accordingly. Based on the explanation above, the writer will make a construction project expenditure management application design at PT. Begawan Polosoro is based on android so that employees who are entrusted with large amounts of money can carry out their work properly and report the use of the money directly in the application, so that transparency of funds provided by company owners with funds issued by employees and the total balance of each project carried out is always can be seen and supervised by the owner of the company.